Transformation of the Ukrainian Institutional Apparatus Between 2017 and 2022 - Fuentes Acosta, Alberto Adrian (Université d'Ottawa | University of Ottawa, 2026)
This thesis examines the transformation of Ukraine’s institutional apparatus between 2017 and 2022, a period marked by significant political, legal, and economic reforms. Focusing on the transition from Petro Poroshenko’s presidency to Volodymyr Zelensky’s administration, the study analyzes how internal and external pressures, including civil society mobilization and conditionality from Western organizations such as the European Union, NATO, the World Bank, and the International Monetary Fund, shaped the restructuring of Ukraine’s governance framework. Key reforms, including the 2021 Anti-Oligarch Act, judicial and land market reforms, and the creation of specialized anti-corruption institutions, are assessed for their impact on dismantling entrenched patronal networks and advancing transparency and accountability. Employing a qualitative methodology grounded in comparative politics and international relations, the thesis integrates empirical and theoretical perspectives to explain the dynamics of institutional change in a hybrid regime. The findings highlight the resilience of informal power structures, the ambivalent role of the presidency, and the critical influence of civil society and external actors in driving reform. Ultimately, the study contributes to understanding the complexities of institutional transformation in post-Soviet states and offers insights into Ukraine’s ongoing pursuit of democratic consolidation and European integration.
Keywords: Ukraine; Institutional transformation; Patronal democracy; Anti-corruption; Oligarchs; European integration; Civil society; External conditionality; Hybrid regime; Systema; Governance